Compatibility of mathematics study subjects in ŠU and ŠSC - Kačinskaitė, Roma; Rimkevičienė, Audronė (Lietuvos matematikos rinkinys, 2011)
In the article, main attention is given to the compatibility of study subjects of mathematics in studies programs of physical sciences “Business Informatics” and “Informatics”‘ at Šiauliai State College and Šiauliai University, respectively. Also, we review the normative documents regulating the order of study results in higher education.